Geological structures of large landslides in Japan - Chigira, Masahiro (Journal of Nepal Geological Society, 2000)
There are many large catastrophic landslides and volcanic collapses in Japan. In this paper, the large landslides (with volumes more than a million cubic metres) are categorised into three groups based on their geological structure, slope morphology, and triggering factors. The first type of landslide occurs on a cataclinal slope where the slope and bedding (or foliation) are dipping in the same direction. The landslide occurring on such a slope may be preceded by scarplets with arcuate trace convex upslope on a plan view. The second type of slide is found on a slope with bedding or foliation that dips steeply in the depth and is toppled towards the valley due to mass rock creep. This kind of rock deformation is recognised to precede many landslides in Japan with its geomorphological expressions of linear depressions and multiple ridges. The third type of landslide is found on the slope with a thick cap rock of limestone and/or greenstone underlain by a chaotic mixture of mudstone with scaly cleavage and rock blocks of sandstone and chert.